Endothelial SIRT1 prevents age-induced impairment of vasodilator responses by enhancing the expression and activity of soluble guanylyl cyclase in smooth muscle cells. Issue 3 (27th August 2018) - Guo, Yumeng; Xu, Cheng; Man, Andy W C; Bai, Bo; Luo, Cuiting; Huang, Yu; Xu, Aimin; Vanhoutte, Paul M; Wang, Yu
Abstract: Aims: Aged arteries are characterized by attenuated vasodilator and enhanced vasoconstrictor responses, which contribute to the development of diseases such as arterial hypertension, atherosclerosis, and heart failure. SIRT1 is a longevity regulator exerting protective functions against vascular ageing, although the underlying mechanisms remain largely unknown. This study was designed to elucidate the signalling pathways involved in endothelial SIRT1-mediated vasodilator responses in the arteries of young and old mice. In particular, the contributions of nitric oxide (NO), endothelial NO synthase (eNOS), cyclooxygenase (COX), and/or soluble guanylyl cyclase (sGC) were examined. Methods and results: Wild type (WT) or eNOS knockout (eKO) mice were cross-bred with those overexpressing human SIRT1 selectively in the vascular endothelium (EC-SIRT1). Arteries were collected from the four groups of mice (WT, EC-SIRT1, eKO, and eKO-SIRT1) to measure isometric relaxations/contractions in response to various pharmacological agents. Reduction of NO bioavailability, hyper-activation of COX signalling, and down-regulation of sGC collectively contributed to the decreased vasodilator and increased vasoconstrictor responses in arteries of old WT mice. Overexpression of endothelial SIRT1 did not block the reduction in NO bioavailability but attenuated the hyper-activation of COX-2, thus protecting mice from age-induced vasoconstrictor responses in arteries of EC-SIRT1 mice. Deficiency of eNOS did not affect endothelial SIRT1-mediated anti-contractile activities in arteries of eKO-SIRT1 mice. Mechanistic studies revealed that overexpression of endothelial SIRT1 enhanced Notch signalling to up-regulate sGCβ1 in smooth muscle cells. Increased expression and activity of sGC prevented age-induced hyper-activation of COX-2 as well as the conversion of endothelium-dependent relaxations to contractions in arteries of EC-SIRT1 mice. Conclusion: Age-induced down-regulation of sGC and up-regulation of COX-2 in arteries are at least partly attributable to the loss-of-endothelial SIRT1 function. Enhancing the endothelial expression and function of SIRT1 prevents early vascular ageing and maintains vasodilator responses, thus representing promising drug targets for cardiovascular diseases.